Variants in SNCA Gene Are Associated with Parkinson’s Disease Risk and Cognitive Symptoms in a Brazilian Sample - Campêlo, Clarissa L.C; Cagni, Fernanda C.; de Siqueira Figueredo, Diego; Oliveira Jr., Luiz G.; Silva-Neto, Antônio B.; Macêdo, Priscila T.; Santos, José R.; Izídio, Geison S.; Ribeiro, Alessandra M.; de Andrade, Tiago G.; de Oliveira Godeiro, Clécio; Silva, Regina H. (Frontiers in Aging Neuroscience, 2017)
Genetic susceptibility contributes to the etiology of sporadic Parkinson´s Disease (PD) and worldwide studies have found positive associations of polymorphisms in the alpha-synuclein gene (SNCA) with the risk for PD. However, little is known about the influence of variants of SNCA in individual traits or phenotypical aspects of PD. Further, there is a lack of studies with Latin-American samples. We evaluated the association between SNCA single nucleotide polymorphisms (SNPs - rs2583988, rs356219, rs2736990 and rs11931074) and PD risk in a Brazilians sample. In addition, we investigated their potential interactions with environmental factors and specific clinical outcomes (motor and cognitive impairments, depression and anxiety). A total of 105 PD patients and 101 controls participated in the study. Single locus analysis showed that the risk allele of all SNPs were more frequent in PD patients (p<0.05), and the associations of SNPs rs2583988, rs356219 and rs2736990 with increased PD risk were confirmed. Further, the G-rs356219 and C-rs2736990 alleles were associated with early onset PD. T-rs2583988, G-rs356219 and C-2736990 alleles were significantly more frequent in PD patients with cognitive impairments than controls in this condition. In addition, in a logistic regression model, we found an association of cognitive impairment with PD, and the practice of cognitive activity and smoking habits had a protective effect. This study shows for the first time an association of SNCA polymorphism and PD in a South-American sample. In addition, we found an interaction between SNP rs356219 and a specific clinical outcome, i.e., the increased risk for cognitive impairment in PD patients.